Dietary lipids with potential to affect satiety: Mechanisms and evidence. Issue 10 (31st May 2019) - Maher, Tyler; Clegg, Miriam E.
ABSTRACT: Dietary fat has been implicated in the rise of obesity due to its energy density, palatability and weak effects on satiety. As fat is a major contributor to overall energy intake, incorporating fat with satiating properties could potentially reduce energy intake. This review outlines the potential mechanisms, as far as we know, by which Medium-Chain Triglycerides (MCT), Conjugated Linoleic Acid (CLA), Short-Chain Fatty Acids (SCFA), Diacylglycerol (DAG), n -3 PUFA, and Small Particle Lipids, exerts their satiating effects. The evidence suggests that the lipid with the most potential to enhance satiety is MCT. SCFA can also promote satiety, but oral administration has been linked to poor tolerability rather than satiety. Data on the appetite effects of CLA is limited but does suggest potential. Research comparing these lipids to each other is also lacking and should be explored to elucidate which of these 'functional lipids' is the most beneficial in enhancing satiety.